1986
DOI: 10.1136/thx.41.12.932
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography based estimates of regional gas and tissue volume of the lung in supine subjects with chronic airflow limitation or fibrosing alveolitis.

Abstract: Twelve patients with chronic airflow limitation and 12 patients with a histological diagnosis of fibrosing alveolitis were studied. The calculated mean (SD) tissue volume of a single lung at total lung capacity was 467 (91) ml in the patients with alveolitis, which was 43% (14%) more than predicted for healthy people of the same age, sex, and height. The tissue volume of a single lung at total lung capacity was 436 (82) ml in the patients with chronic airflow limitation, which was 26% (21%) more than predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…The groups of emphysema patients with high M and normal M had a slightly positive but nonsignificant craniocaudal gradient of D between the apex and 80% lung height, whereas the group with low M had an absence of gradient (Fig 3, middle, b). Although the gradient of D observed at low lung volume 9,10,23 in healthy subjects as well as in emphysema patients has been shown to be reduced with lung inflation at TLC, our observations indicated that this gradient might be abolished even at FRC in emphysema patients who have severe, destructive losses of lung tissue.…”
Section: Differences Between the Patient Groupscontrasting
confidence: 57%
See 1 more Smart Citation
“…The groups of emphysema patients with high M and normal M had a slightly positive but nonsignificant craniocaudal gradient of D between the apex and 80% lung height, whereas the group with low M had an absence of gradient (Fig 3, middle, b). Although the gradient of D observed at low lung volume 9,10,23 in healthy subjects as well as in emphysema patients has been shown to be reduced with lung inflation at TLC, our observations indicated that this gradient might be abolished even at FRC in emphysema patients who have severe, destructive losses of lung tissue.…”
Section: Differences Between the Patient Groupscontrasting
confidence: 57%
“…Although there are numerous reports on the ventrodorsal gradient of D, few studies have been devoted to the craniocaudal density gradient of human lungs in subjects with emphysema. 9,10 To our knowledge, the interrelationship between both the severity and extent of emphysema (Xt) and the distributions of tissue mass and air volume in this gradient have not been investigated previously.…”
mentioning
confidence: 99%
“…Detailed information about (regional) lung volumes and lung density can be oblained from computed tomography, single-photon emission computed tomography and magnetic resonance inlaging [200][201][202][203], bul tl1ese techniques for determining lung volumes are still at an experimental stage. 4 Bronchodilator response and serial measurements…”
Section: 9mentioning
confidence: 99%
“…Other investigators showed that at suspended inspiration a density gradient could be measured within the gravity plane that compared very favourably to pleural pressure gradients that had been described using inhaled radioactive Xenon 3,4 . Importantly, these and other studies have shown that as disease develops the density of the lung changes and that these density changes are related to lung function 5,6 . Therefore, the superior resolution of CT images and the ability to obtain quantitative information helped propel CT densitometry analysis into the mainstream such that CT became a popular and central part of many lung structure/function studies in health and disease.…”
Section: Introductionmentioning
confidence: 60%